Settling velocity of a porous object - Muhammad Khalil Khaidir (2015)
Stokes’ Law can be used generally to analytically determine the settling velocity of a particle of a typical regular shape such as a sphere. Such objects are also generally assumed to be homogenous in term of mass distribution. In actual situations, particles found in wastewater which are commonly called flocs are porous which means that there are cavities within the particles that allow advection flow through it. The presence of porosity would therefore render Stokes’ law inadequate for calculating the terminal settling velocity for the laminar flow case. Lim (2014) experimentally determined the settling velocity of porous spheres constructed with alloy wires. The shape and size of the spheres were kept constant and only the porosity varies. The settling experiments were conducted under different fluid viscosities and a curve was plotted which relates Drag Coefficient (CD) with Reynolds Number (Re) and porosity. As a continuation of Lim’s works, different wire materials were used to construct the porous sphere in order to investigate the possible effects of material properties on its settling velocity. The materials chosen to construct the spheres are copper wire, brass wire and stainless steel wire. Two different sphere sizes of 14 mm and 18 mm were constructed to investigate the effect of different sizes on the settling velocity. The results obtained extend the CD vs. Re curve plotted by Lim to a certain extent. It is shown that the new CD vs. Re curve produced follows the same trend as the one obtained by Lim and thus confirms the reproducibility of her results.